Thyroid Hormone and Leptin in the Testis - Ramos, Cristiane Fonte; Zamoner, Ariane (Frontiers in Endocrinology, 2014)
Leptin is primarily expressed in white adipose tissue; however, it is expressed in the hypothalamus and reproductive tissues as well. Leptin acts by activating the leptin receptors (Ob-Rs). Additionally, the regulation of several neuroendocrine and reproductive functions, including the inhibition of glucocorticoids and enhancement of thyroxine and sex hormone concentrations in human beings and mice are leptin functions. It has been suggested that thyroid hormones (TH) could directly regulate leptin expression. Additionally, hypothyroidism compromises the intracellular integration of leptin signaling specifically in the arcuate nucleus. Two TH receptor isoforms are expressed in the testis, TRa and TRb, with TRa being the predominant one that is present in all stages of development. The effects of TH involve the proliferation and differentiation of Sertoli and Leydig cells during development, spermatogenesis, and steroidogenesis. In this context, TH disorders are associated with sexual dysfunction. An endocrine and/or direct paracrine effect of leptin on the gonads inhibits testosterone production in Leydig cells. Further studies are necessary to clarify the effects of both hormones in the testis during hypothyroidism. The goal of this review is to highlight the current knowledge regarding leptin and TH in the testis.